Interacting protein partners of Arabidopsis RNA‐binding protein AtRBP45b. (20th January 2017) - Muthuramalingam, M.; Wang, Y.; Li, Y.; Mahalingam, R.
Abstract: RNA binding proteins, important players in post‐transcriptional gene regulation, usually exist in ribonuclear complexes. However, even in model systems like Arabidopsis characterisation of RBP associated proteins is limited. In this study, we investigated the interacting proteins of the Arabidopsis AtRBP45b, which is involved in stress signalling. In vivo localisation of AtRBP45b was conducted using 35S‐GFP. FLAG‐tagged AtRBP45b under control of the 35S promoter in the Atrbp45b‐1 mutant background was used to pull down AtRBP45b interacting proteins. Yeast two‐hybrid analysis, fluorescence energy resonance transfer assays were used to confirm the veracity of the AtRBP45b interacting proteins. In planta GFP‐tagging indicated AtRBP45b is localised to the nucleus and the cytosol. AtRBP45b protein has a N‐terminal proline‐rich region and a C‐terminal glutamine‐rich domain that are usually involved in protein–protein interactions. Co‐immunoprecipitation followed by mass spectrometry‐based protein sequencing led to identification of 30 proteins that interacted with AtRBP45b. Using information from interactome databases (BIOGRID, INTACT and STRING), pull‐down assays and localisation data, 12 putative interacting proteins were selected for yeast two‐hybrid analysis. Cap‐binding protein (CBP20, At5g44200) and polyA‐binding protein (PAB8, At1g49760) were shown to interact with AtRBP45b. Based on its interacting partners we speculate that AtRBP45b may play an important role in RNA metabolism, especially in aspects related to mRNA stability and translation initiation during stress conditions in plants.